Examining the Relationship between Inflation Instability and Ecological Footprint: Evidence from Turkey - Beşe, Emrah; Friday, H. Swint; Kalaycı, Salih (International Journal of Energy Economics and Policy, 2024)
Sustainability is a preeminent global issue. This study delves into sustainability with an examination of the effect of inflation instability on ecological footprint per capita through financial development, economic growth, and energy consumption by using the ARDL model for Turkey for the period 1980 through 2015. The results of this study confirmed that financial development and inflation instability improve the environment insignificantly while economic growth does not significantly damage the environment. In addition, energy consumption is found to cause environmental degradation. Results of this study show that the main issue for Turkey is consumption rather than production. Suggested policy-making implications are provided in the conclusion.